TINJAUAN ATAS PENGAKUAN PENDAPATAN DAN PERHITUNGAN HARGA POKOK PENJUALAN PADA PT DINAMIKA ENERGY INDONESIA - Sephia Siska Nurul Hermawati (2023)
PSAK 72 revenue is defined as income arising during the process of company activity. Basically, PSAK No. 72 revenue from contracts with customers consists of 5 stages, namely identifying contracts with customers, determining executor obligations, determining transaction prices, allocating transaction prices to executing obligations, and recognizing revenue when the entity has completed executor obligations. Cost of goods produced is the financing charged in producing a good or service. In this writing, some data and information are obtained at the data collection stage, through observation, interviews, and documentation. PT. Dinamika Energy Indonesia is still implementing PSAK 23 using the accrual basis method, revenue recognition occurs when revenue invoices are issued and only then get revenue. Already implementing PSAK 72 revenue from contracts with customers consists of 5 stages. In the full costing method, production determination financing is the cost of raw materials, direct labor costs, and factory overhead costs , fixed costs and variable costs.